Capitalism in contrasting cultures - Clegg, Stewart; Redding, S. G.; Cartner, Monica, 1944- (De Gruyter studies in organization, 1990)
"Selected papers from a conference held in Hong Kong in April 1988, titled 'Firms, Management, the State and Economic Cultures'. It was organized within the Department of Management Studies of the University of Hong Kong under the auspices of APROS (Australian and Pacific Researchers in Organization Studies)"--Preface